Burgers in Blackface Anti-Black Restaurants Then and Now - Kwate, Naa Oyo A. (Forerunners: Ideas First, 2019)
Exposes and explores the prevalence of racist restaurant branding in the United States Aunt Jemima is the face of pancake mix. Uncle Ben sells rice. Chef Rastus shills for Cream of Wheat. Stereotyped Black faces and bodies have long promoted retail food products that are household names. Much less visible to the public are the numerous restaurants that deploy unapologetically racist logos, themes, and architecture. These marketing concepts, which center nostalgia for a racist past and commemoration of our racist present, reveal the deeply entrenched American investment in anti-blackness. Drawing on wide-ranging sources from the late 1800s to the present, Burgers in Blackface gives a powerful account, and rebuke, of historical and contemporary racism in restaurant branding. Forerunners: Ideas First Short books of thought-in-process scholarship, where intense analysis, questioning, and speculation take the lead